Characterization of an Endophytic Strain Talaromyces assiutensis, CPEF04 With Evaluation of Production Medium for Extracellular Red Pigments Having Antimicrobial and Anticancer Properties - Mishra, Rahul Chandra; Kalra, Rishu; Dilawari, Rahul; Deshmukh, Sunil Kumar; Barrow, Colin J.; Goel, Mayurika (Frontiers in Microbiology, 2021)
Considering the worldwide demand for colorants of natural origin, the utilization of ascomycete fungi as a prolific pigment producer unfolds a novel way to obtain these pigments for various applications, including food, cosmetic, and medical use. The presence of very few natural red pigment alternatives in the market also attracts research and industry priorities to unearth novel and sustainable red pigment producers. The present work is an attempt to identify a novel source of red color obtained from endophytic fungi isolated from terrestrial and marine habitats. Based upon the fungal capacity for pigment production, seven isolates of endophytic fungi were recognized as prospective pigment producers. Out of all, fungal isolate CPE04 was selected based upon its capacity to produce profuse extracellular red pigment. The isolate was identified as Talaromyces assiutensis, employing morphological features and phylogenetic characterization by internal transcribed spacer (ITS) sequences. To understand the chemical behavior of pigment molecules, an investigation of the chemical profile of fungal culture filtrate dried powder (CFDP) was performed using ultra-high-performance liquid chromatography-diode array detector-mass spectrometry (UPLC–DAD–MS). In total, eight compounds having pigment and pharmaceutical application were tentatively identified using UPLC–DAD–MS. Considering the commercial aspect of the stated work, an effort was also made for standardizing the upscaling of the pigment molecule. Investigations were performed for optimum medium and culturing conditions for maximum pigment production. CFDP was found to have a significant antibacterial activity against the bacterial pathogens Staphylococcus aureus (MTCC737), Vibrio cholerae (N16961), and methicillin-resistant S. aureus (MRSA) (ATCC BAA811). The CFDP showed a minimum inhibitory concentration at 64, 128, and 256 μg/ml against S. aureus, MRSA, and V. cholerae. A concentration-dependent (50–400 μg/ml) anticancer effect on HeLa cancer line was also observed, having a half-maximal inhibitory concentration (IC50) at 300 μg/ml. The antioxidant potential of CFDP has also been proven with the help of an antioxidant assay against 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) radical (IC50, 32.01 μg/ml); DNA nicking assay and reactive oxygen species were generated in HeLa cancer line cells. The CFDP was also found to have no cytotoxicity toward HEK 293 T cell line using alamar blue (resazurin), a cell metabolic activity reagent.